The Euro Experience and Lessons for Latin America - Hurtado, Carlos (World Bank, Washington, DC, 2014)
It is natural to think, and economic theory predicts, that integration in an economic zone like Europe fosters growth and development, particularly when integration refers to trade opening among countries. It is expected that openness (to trade) promotes growth and being closed (to trade) deters it. Trade theory also concludes that (trade) integration is beneficial to all countries, large and small, and that small economies are likely to benefit relatively more from integration. This note reviews the development of the European Union's euro zone and its impacts on growth and finds lessons that can be useful for Latin America.